Epidemiological Aspects of Imported Melioidosis in Korea and Japan, 2011 to 2020 - Myeong-Jin Lee; Kyu Sung Kim; Won-Chang Lee; Young Hwan Kwon (Hanggong uju uihakoeji, 2023)
Purpose: Melioidosis is a zoonosis that can infect humans or animals. The disease is caused by the bacteria Burkholderia pseudomallei, which is found in contaminated soil and water. We investigated the epidemiological aspects of melioidosis cases among oversea travelers in Korea and Japan during 2011 to 2020. Methods: Raw data were obtained from the website of melioidosis cases from the Korea Diseases Control and Prevention Agency, and the National Institute of infectious Diseases in Japan, 2011−2020. Results: There were 26 cases of melioidosis cases in Korea and 14 cases in Japan between 2011 and 2020. Cumulative incidence rate per 1,000,000 oversea travelers (OTs) of Korea (0.14) did not substantially differ that of Japan (0.09), respectively. The incidence of melioidosis in males (96.2% of total 26 cases) was much more common than in females (3.8%) in OTs of Korea (P<0.01), while there were significant differences level between males (85.7% of total 14 cases) and females (14.3%) in OTs of Japan (P<0.01). On the other hand, the distribution by adjusted-age groups for melioidosis cases were statistically similar distribution between Korean and Japanese that total cases occurred in the over 40-years old age, clearly showing a more infected of melioidosis (P<0.05). Conclusion: This study demonstrates that there is a similar pattern of imported melioidosis cases in Korea and Japan. Therefore, to prevent melioidosis infections, greater attention should be paid to individuals who are planning to travel to the presumptive regions of melioidosis.